Effect of carbon on the properties of CrN coatings formed by cathodic arc evaporation in stationary system - Kuprin, A.S.; Kolodiy, I.V.; Ovcharenko, V.D.; Tolmachova, G.N.; Gilewicz, A.; Lupicka, O.; Warcholinski, B. (Вопросы атомной науки и техники, 2016)
Due to good resistance to oxidation and wear chromium nitride coatings are widely used in industry. The works
aimed at further improving, for example by carbon doping, the properties of the coatings. The goal of this study was
to assess effect of carbon addition to CrN coatings deposited without substrates rotation on the deposition rate,
roughness, structure, hardness, adhesion, wear and comparison with properties of CrN coating. Покрытия из нитрида хрома широко используются в промышленности благодаря хорошей стойкости к
окислению и износу. Выполняются работы, направленные на дальнейшее совершенствование свойств
покрытий, например, путем легирования углеродом. Цель данного исследования состоит в том, чтобы
оценить влияние легирования углеродом CrN-покрытий, наносимых без вращения подложки, на скорость
осаждения, шероховатость, структуру, твердость, адгезию и износ, а также сравнить со свойствами CrN-
покрытия. Покриття з нітриду хрому широко використовуються в промисловості завдяки хорошій стійкості до
окислення і зносу. Виконуються роботи, спрямовані на подальше вдосконалення властивостей покриттів,
наприклад, шляхом легування вуглецем. Мета даного дослідження полягає в тому, щоб оцінити вплив
легування вуглецем CrN-покриттів, що наносяться без обертання підкладки, на швидкість осадження,
шорсткість, структуру, твердість, адгезію і знос, а також порівняти з властивостями CrN-покриття.